Embryonic Heart Development in Play-Doh - Elmus Beale (Association of American Medical Colleges, 2010)
Abstract This resource uses Play-Doh to sequentially illustrate (1) folding of the heart tube into a primitive heart, (2) septation of the primitive ventricles and outflow tract by the truncoconal septum, and (3) septation of the primitive atrium by the septum primum and septum secundum. The resource includes an instructor's guide and a 3-minute, 46-second video in three different formats: ordinary MPEG-4, MPEG-4 formatted for smartphones, and QuickTime movie. The video was created as a result of student feedback regarding in-class use of Play-Doh to illustrate various aspects of embryonic development. Students felt that demonstrations using Play-Doh were more effective than textbook illustrations or online animations in helping them to quickly and easily understand complicated developmental sequences. The video is suitable for teaching and reviewing embryology of the heart in several contexts, including, but not limited to, lectures, online study materials, webcasts, and video podcasts. The video does not include a complete explanation of heart development, but it is effective when used in conjunction with any good embryology text. Students reported that the Play-Doh videos help them learn embryology.